Methicillin-resistant Staphylococcus aureus containing mecC in Swedish dairy cows - Unnerstad, Helle Ericsson (BioMed Central, 2013)
BACKGROUND: Hitherto, methicillin-resistant Staphylococcus aureus (MRSA) has not been detected in Swedish cattle. However, due to the report of mecC, a novel homologue to the mecA gene, there was reason to re-evaluate susceptibility results from strain collections of Staphylococcus aureus and test suspected isolates for the presence of mecC. FINDINGS: Bovine isolates of S. aureus with elevated minimum inhibitory concentrations of beta-lactams were retrospectively tested for presence of mecC. In four of the isolates mecC was detected. CONCLUSION: In Sweden, this is the first finding of MRSA in cattle and the first detection of MRSA harbouring mecC of domestic animal origin. MRSA in animal populations has implications as a potential reservoir with risk for spread to humans. Occurrence of MRSA among Swedish cattle appears still very limited.